LINGUISTIC ANALYSIS OF TONGUE TWISTERS WITH NATURAL PHENOMENA COMPONENTS IN THE ENGLISH LANGUAGE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores the linguistic features of English tongue twisters that include natural phenomena components. The research focuses on phonetic, lexical, semantic, and stylistic aspects of such tongue twisters, revealing how natural elements like wind, rain, sun, and snow contribute to sound repetition, rhythm, and imagery. The study also highlights the connection between linguistic structure and cultural perception of nature in English-speaking communities.